The Systemic Banking Crisis of 2014-2015 in Ukraine: Causal Relationship - Biletska Nataliya V.; Lopatiuk Ruslana I.; Servetnik-Tzariy Valentina V. (Problemi Ekonomiki, 2016)
The aim of the article is to study the concept of systemic banking crisis in scientific and practical literature as well as determine the causes and consequences of systemic banking crises on the example of the Ukrainian banking system for the last two years. The definitions of “banking crisis”, “systemic banking crisis” have been considered and our own vision of the theoretical aspect of a systemic banking crisis has been suggested. The features of systemic banking crises, in particular the crisis of 2014—2015, through the prism of social, political, economic, micro- and macroeconomic factors have been identified. The consequences, to which it led the Ukrainian banking system, and its impact on the population living standards have been examined. The dynamics of main indicators of the banking activity in Ukraine over the last five years has been analyzed, and a few basic points, which require the investors’ attention when choosing a bank, have been suggested.